(untitled) (Madhyabindu Journal, 2021)
Information disclosure is an integral to corporate governance, i.e., an important element of corporate governance, since higher disclosure could be able to reduce the information asymmetry, to clarify the conflict of interests between the shareholders and the management, and to make corporate insiders accountable. The study has utilized primary data. In order to collect the primary data, 150 questionnaires were distributed to the customers of 16 Nepalese commercial banks that include private banks, joint venture banks and public banks. The study includes eight non joint venture banks, six joint venture banks and two public banks. The opinion survey reveals that the most of the respondents are convinced about effective corporate governance is linked towards the better level of social information disclosure. The majority of respondents have highlighted that CEO and Chairman must be different for high level of social information disclosure.